2008
DOI: 10.1080/13880200801887138
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofAloe vera. on Rat Pulp Tissue

Abstract: Aloe vera L. (Aloeaceae) has been extensively studied for anti-inflammatory, antimicrobial, and cellular regeneration properties. This work evaluated in vivo the effects of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…A metal foil interface (stainless platinum, 2 mm diameter) was used to prevent detrimental discharge of ionic mercury contained in the final amalgam restorative material (Velvalloy, S.S. White, Ltd., Rio de Janeiro, Rio de Janeiro, Brazil). [11][12]…”
Section: Animalsmentioning
confidence: 99%
“…A metal foil interface (stainless platinum, 2 mm diameter) was used to prevent detrimental discharge of ionic mercury contained in the final amalgam restorative material (Velvalloy, S.S. White, Ltd., Rio de Janeiro, Rio de Janeiro, Brazil). [11][12]…”
Section: Animalsmentioning
confidence: 99%
“…39 In an animal model, Gala-Garcia et al, evaluated the effect of AV on rat pulp tissue and found that they have superior biocompatibility and potential to form tertiary dentinal bridge formation. 40 …”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study [18] that assessed the presence of dentin bridges found that over 90 % of the BCP/PLGA samples showed the presence of dentin bridging and that inflammation was resolved after 30 days. The important effects of HA and b-TCP can be seen in their ability to enhance bone growth, both across a gap and around an implant.…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed according to a previously described protocol [11,18]. Approval for this research was obtained from the Institutional Ethics Committee for Animal Research of Federal University of Minas Gerais.…”
Section: Evaluations Of In Vivo Pulp Responsementioning
confidence: 99%